The origins of early Christian literature: contextualizing the New Testament within Greco-Roman literary culture - Walsh, Robyn Faith (Cambridge University Press, 2021)
Conventional approaches to the Synoptic gospels argue that the gospel authors acted as literate spokespersons for their religious communities. Whether described as documenting intra-group 'oral traditions' or preserving the collective perspectives of their fellow Christ-followers, these writers are treated as something akin to the Romantic poet speaking for their Volk - a questionable framework inherited from nineteenth-century German Romanticism. In this book, Robyn Faith Walsh argues that the Synoptic gospels were written by elite cultural producers working within a dynamic cadre of literate specialists, including persons who may or may not have been professed Christians. Comparing a range of ancient literature, her ground-breaking study demonstrates that the gospels are creative works produced by educated elites interested in Judean teachings, practices, and paradoxographical subjects in the aftermath of the Jewish War and in dialogue with the literature of their age. Walsh's study thus bridges the artificial divide between research on the Synoptic gospels and Classics.